Opinion Leaders and Boycott Intentions: Factors Influencing Consumer Behavior in Support of Israel Boycott - Awaludin, Azrul Afrillana; Al-Khaidar, Moch Aridhi (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
This study aims to identify the factors driving consumers to boycott companies that support the occupation of Israel, with an emphasis on the role of religiosity and religious values as the main motivating factors. This is motivated by contradictory results from previous research, especially related to the influence of religiosity and opinion leaders in boycotting companies that support Israel. The variables under investigation include opinion leaders, religiosity, consumer animosity, consumer ethnocentrism, and perceived efficacy, measured using a 5-point Likert scale. The research method is quantitative, employing SEM-PLS for model evaluation. A total of 156 respondents were selected through the purposive sampling technique. The research findings conclude that, among the five independent variables, religiosity, consumer animosity, and opinion leaders do not have a direct influence on the intention to boycott. However, opinion leaders indirectly influence the boycott intention through consumer ethnocentrism. Meanwhile, consumer ethnocentrism and perceived efficacy positively influence the intention to boycott. This research contributes to the literature on the role of opinion leaders in shaping consumer behavior and provides an actual understanding of the boycott phenomenon. In practical terms, this research makes an implication contribution to supporting local products by utilizing opinion leaders as promoters